On The Dynamics of Discrete-Time Prey-Predator System with Ratio-Dependent Functional Response - Naji, Raid (Iraqi Journal of Science, 2023)
In this paper, a discrete- time ratio-dependent prey- predator model is proposed and analyzed. All possible fixed points have been obtained. The local stability conditions for these fixed points have been established. The global stability of the proposed system is investigated numerically. Bifurcation diagrams as a function of growth rate of the prey species are drawn. It is observed that the proposed system has rich dynamics including chaos.